A Caregivers’ Strategies in Shaping Students’ Religious Character Based on the Boarding School Program at MAN 2 Kota Bima: Caregivers’ Strategies in Shaping Students’ Religious Character Based on the Boarding School Program - Rijalul Rahman (Journal of Educational Studies, 2026)
Abstract This study analyzes caregivers’ strategies in shaping students’ religious character through the boarding school program at MAN 2 Kota Bima. This research focuses on exemplary behavior, habituation, and supervision applied by caregivers in students’ daily activities, as well as the integration of Arabic and English language practices in supporting communication skills. A qualitative descriptive method was used. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing with triangulation for validity. The findings show that caregivers consistently shape students’ religious character through role modeling, routine religious activities, and continuous supervision in the boarding school environment. Students are trained in discipline, worship practices, and moral behavior through daily habituation. In addition, Arabic and English programs such as daily conversation and muhadharah help improve students’ confidence and communication abilities. The study also finds that religious character formation and language learning are integrated in daily boarding school activities. This study concludes that caregivers’ strategies effectively support the formation of religious character and communication skills among students in the boarding school program.